2001
DOI: 10.1063/1.1394719
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband photoconductive detection: Comparison with free-space electro-optic sampling

Abstract: The spectral response of a low-temperature-grown GaAs photoconductive (PC) antenna is compared with that of the electro-optic sampling technique for the frequency region up to 40 THz. The spectral response of the PC antenna for broadband detection is found to be determined by the temporal profile of the number of photocarriers injected by ultrashort optical gate pulses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 11 publications
0
67
0
Order By: Relevance
“…The laser pulse generates free charge carriers in the semiconductor substrate, which are accelerated by E THz thus generating a current I between two contacts. Assuming a laser pulse of the form sech 2 (1.76t/t 0 ) where t 0 is the full-width-athalf-maximum, the current measured through contact i in the photoconductive receiver described here, is related to E THz by 15 :…”
mentioning
confidence: 99%
“…The laser pulse generates free charge carriers in the semiconductor substrate, which are accelerated by E THz thus generating a current I between two contacts. Assuming a laser pulse of the form sech 2 (1.76t/t 0 ) where t 0 is the full-width-athalf-maximum, the current measured through contact i in the photoconductive receiver described here, is related to E THz by 15 :…”
mentioning
confidence: 99%
“…First attempts of low-temperature growth of In 0.53 Ga 0. 47 As lattice matched to InP substrates were performed in [98]. It has been found that the layers grown at the lowest temperatures (180 o C) were characterised by rather short carrier lifetimes of~2.3 ps, but had very low resistivity.…”
Section: Ingaasmentioning
confidence: 99%
“…Indeed, LTG GaAs and related materials match most of the requirements for making efficient ultrafast optoelectronic devices such as short carrier lifetime, high electron mobility, high electric breakdown field, and large dark resistivity [42]. Components manufactured from LTG GaAs have been used for subpicosecond electric pulse generation [43], all optical switching [44], laser mode locking [45], and, most importantly, for generation and detection of THz pulses with extremely broad frequency bands [46,47] as well as for narrow-band CW THz generation [48].…”
Section: Radiation-damaged Silicon-on-sapphirementioning
confidence: 99%
See 2 more Smart Citations